Men's experiences of receiving a prostate cancer diagnosis after opportunistic screening—A qualitative descriptive secondary analysis. (27th July 2022) - Gellerstedt, Linda; Langius‐Eklöf, Ann; Kelmendi, Nazmije; Sundberg, Kay; Craftman, Åsa G.
Abstract: Background: Prostate cancer is one of the most common types of cancer in men and could occur without symptoms. Screening has been debated but remains controversial and, in most countries, organized population‐based screening does not exist. The aim of this study was to describe men's experiences of receiving a prostate cancer diagnosis after opportunistic screening. Methods: This study is a secondary analysis from interviews with 17 men (aged 56–80 years) who had undergone curative treatment for prostate cancer. Data were collected in an urban region of Sweden through interviews conducted face to face or by telephone. An inductive content analysis was used with Consolidated criteria for Reporting Qualitative research as a reporting checklist. Results: Two main categories were identified. Screening is a lifesaver enclosed by ethical dilemmas reflects how men considered screening as a lifesaving test. Testing was surrounded by injustice and an eagerness to encourage other men to undergo screening. Facing challenges during diagnosis reflects the men's experiences of being in an unknown field yet expected to engage in decision‐making concerning appropriate treatment. Receiving the diagnosis rendered mixed emotions about having a cancer disease, that the treatment could cause lifelong symptom distress and the men described being hesitant to talk about their diagnosis. Conclusions: The findings highlight men's opinions about screening and that the lack of routine screening represents injustice. The men considered this as an ethical question of lifesaving justice, while stakeholders may argue that screening could lead to unnecessary suffering and overtreatment. Men do not always talk openly about their diagnosis, linked to the fact that it concerns intimate areas. It is important to balance the information in relation to shared decision‐making regarding treatment. Health care professionals have an ethical responsibility to support and coach the patient in their decision. Patient or Public Contribution: This study was based on interviews with men who had experienced a diagnosis of prostate cancer.